Understanding the Electrochemical Carbon Dioxide Reduction Reaction Mechanism of Lattice Tuning of Copper by Silver Single‐Crystal Surface - Zheng, Tao; Zhang, Xia‐Guang (Chemphyschem, 2025)
Intermolecular interactions and adsorbate coverage on a metal electrode's surface/interface play an important role in CO2 reduction reaction (CO2RR). Herein, the activity and selectivity of CO2RR on bimetallic electrode, where a full monoatomic Cu layer covers on Ag surface (CuML/Ag) are investigated by using density functional theory calculations. The surface geometric and electronic structure results indicate that there is high electrocatalytic activity for CO2RR on the CuML/Ag electrode. Specifically, the CuML/Ag surface can accelerate the H2O and CO2 adsorption and hydrogenation while lowering the reaction energy of the rate‐determining step. The structure parameters of chemisorbed CO2 with and without H2O demonstrate that activated H2O not only promotes the C−O dissociation but also provides the protons required for CO2RR on the CuML/Ag electrode surface. Furthermore, the various reaction mechanism diagrams indicate that the CuML/Ag electrode has high selectivity for CO2RR, and the efficiency of products can be regulated by modulating the reaction's electric potential. Formation of full monatomic copper layer on the silver surfaces, which has good selectivity and high activity for CO2RR. The adsorbed H2O not only provides the proton required for CO2RR, but also facilitates the adsorption and dissociation of CO2. The coverage and adsorption energy of CO can impact the competing processes between C−C coupling and CO reduction.